Management of intra-abdominal-infections: 2017 World Society of Emergency Surgery guidelines summary focused on remote areas and low-income nations - Gennaro Perrone; Massimo Sartelli; Giuffrida Mario; Alain Chichom-Mefire; Francesco Maria Labricciosa; Fikri M. Abu-Zidan; Luca Ansaloni; Walter L. Biffl; Marco Ceresoli; Federico Coccolini; Raul Coimbra; Zaza Demetrashvili; et al. (International Journal of Infectious Diseases, 2020)
Background: Most remote areas have restricted access to healthcare services and are too small and remote to sustain specialist services. In 2017, the World Society of Emergency Surgery (WSES) published guidelines for the management of intra-abdominal infections. Many hospitals, especially those in remote areas, continue to face logistical barriers, leading to an overall poorer adherence to international guidelines. Methods: The aim of this paper is to report and amend the 2017 WSES guidelines for the management of intra-abdominal infections, extending these recommendations for remote areas and low-income countries. A literature search of the PubMed/MEDLINE databases was conducted covering the period up until June 2020. Results: The critical shortages of healthcare workers and material resources in remote areas require the use of a robust triage system. A combination of abdominal signs and symptoms with early warning signs may be used to screen patients needing immediate acute care surgery. A tailored diagnostic step-up approach based on the hospital's resources is recommended. Ultrasound and plain X-ray may be useful diagnostic tools in remote areas. The source of infection should be totally controlled as soon as possible. Conclusions: The cornerstones of effective treatment for intra-abdominal infections in remote areas include early diagnosis, prompt resuscitation, early source control, and appropriate antimicrobial therapy. Standardization in applying the guidelines is mandatory to adequately manage intra-abdominal infections.